Initial assessment of indoor environmental condition and thermal comfort of Malaysia heritage mosque - Wardah Fatimah Mohammad Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2020)
Heritage mosques are the gems of the country as they preserve the history of local communities and nation. Many studies have been executed on the architectural characteristics of Malaysia heritage mosques. However, the empirical studies on its indoor environmental condition and thermal comfort are still lacking. Therefore, the objective of this study is to identify the indoor environmental condition and thermal comfort of Malaysia heritage mosque by using the field measurement method. The selected heritage mosque for this study is Masjid Tanah, which is located at Masjid Tanah, Alor Gajah, Melaka. Two multiparameter ventilation meters were used in the field measurement. The variables measured were air temperature and air velocity, while the indoor predicted comfort temperature was calculated using the adaptive thermal comfort model equation. The results show that the average indoor air temperatures were lower than the average outdoor air temperatures throughout the measurement. This is also similar with the indoor air velocities which were lower than the outdoor wind speeds at all times. Meanwhile, the results also demonstrate that the average indoor air temperatures were also lower than the indoor predicted comfort temperatures during the morning hours until 1 pm. The overall findings indicate that the architectural characteristics of the selected heritage mosque has a good response to the local climate. However, some improvements are necessary in enhancing the indoor thermal comfort. The findings can be used as guides for achieving a more comfortable indoor environmental condition of heritage mosques, as well as the modern mosques also.